Kekerasan Seksual dan Subordinasi terhadap Perempuan Dibawah Umur: Analisis Berdasarkan UU Nomor 12 Tahun 2022 - Anggi Yulia; Safira Natasya; Ika Arinia Indriyany (Deposisi: Jurnal Publikasi Ilmu Hukum, 2026)
Sexual violence against women and children is still a serious problem in Indonesia. Girls are among the most vulnerable groups because of their young age, emotional dependence, and the imbalance of power with perpetrators who are generally older or close to the victim. Cases of violence often occur in various environments, such as within the family, early marriage, or social relationships such as dating or friendships with older men. This situation often places girls in a weak position, making it difficult for them to resist or report the violence they experience. This research aims to examine forms of sexual violence against girls in relationships with large age differences and examine legal protection based on Law Number 12 of 2022 concerning Crimes of Sexual Violence. The research uses qualitative methods through literature study by reviewing books, scientific journals, regulations, and data from the Ministry of Women's Empowerment and Child Protection. The results of the study show that unequal age relations often give rise to power inequalities that trigger domination, control and various forms of violence, such as sexual coercion, physical violence, psychological manipulation and domestic exploitation. The TPKS Law plays an important role as a basis for legal protection and fulfillment of rights for victims